Determining Accounting Undergraduates' Intention to Become Shariah Auditors in Malaysia: A Theory of Planned Behavior Approach - Ahmad, Maizatul Akmam; Mohamad, Azlinda; Mohamad, Aznizai; Mohamad, Nor Raihan; Mohamad, Azlizan Adila (Advances in Social Sciences Research Journal, 2025)
This study investigates accounting students’ intention to become Shariah auditors based on the Theory of Planned Behavior encompassing attitude, subjective norms, and perceived behavioral control. It identifies the key factors influencing this career intention. Employing data of 127 accounting students across three Malaysian universities and utilizing analysis through Smart PLS, the study reveals that subjective norms and perceived behavioral control significantly impact students' intention to become Shariah auditors. These findings provide valuable insights for universities to enhance accounting curricula and programs, ultimately fostering a workforce proficient in Shariah principles and auditing. Additionally, the findings of the study aid in the development of skilled and competent Shariah auditors equipped to address the growing demands of the Islamic finance sector, thus benefiting academia, the industry, and future practitioners.